It’s Like Doing Simultaneous Mind Puzzles: Exploring How Care is Understood and Experienced by Nursing Assistants Working in Sweden with Older Persons - Lilienthal A; Farias L; Boström AM; Patomella AH; Asaba E (Journal of Multidisciplinary Healthcare)
Anneliese Lilienthal,1 Lisette Farias,1 Anne-Marie Boström,2– 4 Ann-Helen Patomella,1,5 Eric Asaba1,3,6 1Department of Neurobiology, Care Science and Society (NVS), Division of Occupational Therapy, Karolinska Institutet, Stockholm, Sweden; 2Department of Neurobiology, Care Science and Society (NVS), Division for Nursing, Karolinska Institutet, Stockholm, Sweden; 3Unit for Research, Education, Development and Innovation, Stockholms Sjukhem Foundation, Stockholm, Sweden; 4Theme Inflammation and Aging, Karolinska University Hospital, Stockholm, Sweden; 5Academic Primary Health Care Centre (APC), Stockholm Region, Sweden; 6Department of Health and Rehabilitation, University of Gothenburg, Gothenburg, SwedenCorrespondence: Anneliese Lilienthal, Department of Neurobiology, Care Sciences, and Society, Division of Occupational Therapy, Karolinska Institutet, Huddinge, 141 83, Sweden, Email Anneliese.Lilienthal@ki.seBackground: The care of older persons is facing several challenges, especially as care tasks are becoming increasingly rationalized with less opportunity for relational engagement between nurse assistants and older persons. Evidence suggests this engagement is needed to promote well-being and satisfaction among the older persons with whom they work. The aim of this study was to explore how care, in the context of worker perspectives, is understood and experienced in home or residential care facilities.Participants and Methods: Focus-group interviews were conducted with experienced nursing assistants (n = 14) working in urban municipalities in Sweden. Data were analyzed using reflexive thematic analysis.Findings: The main theme: “This work is more than a checklist of tasks, it’s like simultaneous mind puzzles”, exposes the shortcomings of a “task and time” oriented care system while expecting individualized relational care practices. Three subthemes emerged: “It’s about responsibility, not remuneration”, “Knowing them is part of the job” and “We do a lot that is not our job”. Participants expressed working responsibly day-to-day to find solutions to meet the needs of older persons. Tensions experienced between task and relational care orientations align to variation in understandings of care. These subthemes highlight that their work requires being context-sensitive to adapt in the moment, much like trying to solve mind puzzles.Conclusion: Increased rationalization of care, while expecting focus on relational aspects, sets nursing assistants in a challenging position. This paradox negatively affects the health of nursing assistants by creating unsustainable work. Without recognition of the required cognitive engagement in problem solving that is part of their work, the challenges of retention, sick leave and burnout are unlikely to be addressed. To ensure coordinated continuative care for older persons, nursing assistants need time and agency to enact relational practices that facilitate doing their work’s dynamic care puzzles.Keywords: assistant nurse, homecare, residential care, work, relational care, fundamental care